Kepemimpinan Situasional; Suatu Kajian terhadap konsep Kenneth Blenchard - Hilmi, Hilmi (Media Akademika, 2001)
This study attemps to analyze the concept of Situational Management founded by Kenneth Blanchard by means of Content Analysis. Its elaborates managers` behavior in leading, encouraging a company of institution as well as in solving problems form which point the managers are going to make further policy for the company. It also discusses the development of employees by encouraging the employees to improve their skills and spirits in their working places. The author of this study, finally concludes that a manager should vary his of her managerial technigue in working with his of her subordinates in leading, encouraging, colving problems, making decision, as well as improving skill according to the current situation of the companies they are managing.